Efficacy and Safety of Switching to the 2-Drug Regimen Dolutegravir/Lamivudine Versus Continuing a 3- or 4-Drug Regimen for Maintaining Virologic Suppression in Adults Living With Human Immunodeficiency Virus 1 (HIV-1): Week 48 Results From the Phase 3, Noninferiority SALSA Randomized Trial. (2nd March 2022) - Llibre, Josep M; Brites, Carlos; Cheng, Chien-Yu; Osiyemi, Olayemi; Galera, Carlos; Hocqueloux, Laurent; Maggiolo, Franco; Degen, Olaf; Taylor, Stephen; Blair, Elizabeth; Man, Choy; Wynne, Brian; et al.
Abstract: Background: In TANGO, switching to dolutegravir/lamivudine (DTG/3TC) demonstrated long-term noninferior efficacy vs continuing tenofovir alafenamide–based regimens in treatment-experienced adults with HIV-1. The phase 3 SALSA study evaluated efficacy and safety of switching to DTG/3TC compared with continuing various 3-/4-drug current antiretroviral regimens (CARs). Methods: Adults with HIV-1 RNA <50 copies/mL and no previous virologic failure were randomized (1:1, stratified by baseline third agent class) to switch to once-daily fixed-dose combination DTG/3TC or continue CAR (primary endpoint: proportion of participants with HIV-1 RNA ≥50 copies/mL at week 48; Snapshot, intention-to-treat–exposed population, 5% noninferiority margin). Results: Overall, 493 adults (39% women; 39% aged ≥50 years; 19% African American/African heritage; 14% Asian) were randomized to switch to DTG/3TC (n = 246) or continue CAR (n = 247). At week 48, 1 (0.4%) participant in the DTG/3TC group and 3 (1.2%) in the CAR group had HIV-1 RNA ≥50 copies/mL (Snapshot), demonstrating noninferiority (adjusted difference, −0.8%; 95% CI, −2.4%, .8%). Zero participants met confirmed virologic withdrawal criteria; therefore, no resistance testing was performed. Drug-related adverse events were more frequent with DTG/3TC (20%) than CAR (6%) through week 48 but comparable post–week 24 (5% vs 2%, respectively). Proximal tubular renal function and bone turnover biomarkers improved with DTG/3TC. Both groups had generally minimal changes in lipids and inflammatory biomarkers. Conclusions: Switching to DTG/3TC was noninferior to continuing CAR for maintaining virologic suppression at week 48 with no observed resistance, supporting the efficacy, good safety, and high barrier to resistance of DTG/3TC. Clinical Trials Registration: www.clinicaltrials.gov, NCT04021290. Abstract : In treatment-experienced adults without previous virologic failure, switching to the 2-drug regimen dolutegravir/lamivudine was noninferior to continuing current antiretroviral regimens for maintaining virologic suppression at week 48. No confirmed virologic withdrawals or resistance occurred. Dolutegravir/lamivudine had good safety and tolerability. Video Abstract: